Adult Neurogenesis and Parkinson's Disease - Arias-Carrion, Oscar; Freundlieb, Nils; Oertel, Wolfgang H.; Hoglinger, Gunter U. (CNS & Neurological Disorders - Drug Targets, 2007)
Parkinson's disease is a neurodegenerative disorder characterized by a progressive neuronal loss affecting preferentially the dopaminergic neurons of the nigrostriatal projection. Transplantation of fetal dopaminergic precursor cells has provided the proof of principle that a cell replacement therapy can ameliorate clinical symptoms in affected patients. Recent years have provided evidence for the existence of neural stem cells with the potential to produce new neurons, particularly of a dopaminergic phenotype, in the adult mammalian brain. Such stem cells have been identified in so called neurogenic brain areas, where neurogenesis is constitutively ongoing, but also in primarily non-neurogenic areas, such as the midbrain and the striatum, where neurogenesis does not occur under normal physiological conditions. We review here presently published evidence to evaluate the concept that endogenous neural stem cells may have the potential to be instrumentalized for a non-invasive cell replacement therapy with autologous neurons to repair the damaged nigrostriatal dopaminergic projection in Parkinson's disease.
Keywords: regenerative medicine